(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Salinity is a major constraint in crop production in saline prone areas of Bangladesh. Therefore, a study was carried out in order to investigate the effect of different levels of NaCl salinity stress on seed germination and seedling growth of tomato. This study was consisted with five varieties of tomato (BARI Tomato-2, BARI Tomato-3, BARI Tomato-4, BARI Tomato-14, and BARI Tomato-15) and four levels of NaCl salt solution (0, 50, 100 and 150 mM). Seeds were placed in petridish for germination and the seedlings were allowed to grow for ten days. Results showed that percent seed germination decreased with increasing salt concentration in the germinating media. The highest seed germination (68.25%) was recorded in untreated control (0 mM) condition and the lowest in 150 mM salt solution ((5.92%). In combination of variety and salt concentration, BARI Tomato-2 gave the highest germination (88.33%) under 0 mM salinity condition and the lowest (2.92%) in BARI Tomato-3 with 150 mM salt solution. However, percent germination, germination coefficient, radicle and plumule length, seedling vigor index, fresh weight of plumule and radicle, mean germination time, germination index decreased with increasing salt concentration as compared to untreated control condition. The findings indicated that BARI Tomato- 2, BARI Tomato-4 and BARI Tomato-15 were relatively tolerant to salt stress than BARI Tomato-3 and BARI Tomato-14. J Bangladesh Agril Univ 17(4): 490–499, 2019